Factors Of Compliance With Medication in Leprosy Clients in Pamekasan District - Hijriyah, Mufidatul (PT Inovasi Pratama Internasional, 2025)
As an infectious disease that affects the skin and peripheral nerves and is caused by the bacteria mycobacterium leprae as the causative agent. This leprosy is chronic characterized by the presence of white and reddish spots, as well as thickening of the inflamed nerves and impaired nerve function so that it can cause paralysis of the peripheral nerves. This disease first attacks the nervous system, can attack the skin, mucosa (mouth), upper respiratory tract. This bacteria enters the body through the skin or nose. Signs and symptoms of this disease are skin lesions and peripheral nerves that can cause numbness, deformities and permanent disabilities. Objective: To determine the factors of medication adherence in leprosy patients in the Pamekasan area. Method: The design of this study is a cross-sectional study, namely research to determine the relationship between risk factors and disease. In cross-sectional studies, independent variables or risk factors (effects) are assessed simultaneously at one time. Results. obtained in the bivariate test obtained a significance value of 0.000 <0.05 on family support, knowledge, attitudes, environment, and health workers towards leprosy. Conclusion: There is a relationship between family support, knowledge, attitudes, environmental conditions, health workers, and compliance with taking medication in leprosy clients